2018
DOI: 10.1002/hed.25546
|View full text |Cite
|
Sign up to set email alerts
|

Local immune parameters as potential predictive markers in head and neck squamous cell carcinoma patients receiving induction chemotherapy and cetuximab

Abstract: Background The aim of this study was to determine whether tumor‐associated immune cells may predict response to therapy and disease outcome in head and neck squamous cell carcinoma (HNSCC) patients receiving induction chemotherapy and cetuximab. Methods Paraffin‐embedded pretreatment biopsy samples from 45 patients with stage III‐IV resectable HNSCC were investigated retrospectively by immunohistochemistry for density of different immune cell types based on expression of CD8, FOXP3, CD134, CD137, PD‐1, CD20, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
(175 reference statements)
0
10
0
Order By: Relevance
“…To our knowledge, it is the first research to analyze the role of OX40/OX40L in early-stage resectable NSCLC and demonstrate its relationships with PD-1/PD-L1, TILs and patients' clinical outcomes. OX40/OX40L has already been studied previously as an immune characteristic biomarker in some other cancer types, including lymphoma, hepatocellular carcinoma, Leukemia, ovarian, neuroblastoma, head and neck squamous cell carcinoma, gastric cancer and breast cancer (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The TILs OX40 was reported to correlate with patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it is the first research to analyze the role of OX40/OX40L in early-stage resectable NSCLC and demonstrate its relationships with PD-1/PD-L1, TILs and patients' clinical outcomes. OX40/OX40L has already been studied previously as an immune characteristic biomarker in some other cancer types, including lymphoma, hepatocellular carcinoma, Leukemia, ovarian, neuroblastoma, head and neck squamous cell carcinoma, gastric cancer and breast cancer (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The TILs OX40 was reported to correlate with patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…39,45 One study mentioned a higher number of CD56+ NK cells in a study group without metastatic disease. 46 Another study found no correlation between CD16+ NK cells and tumor location, TNM stage, or recurrence of the disease. 44 Supplementary Figure 1.…”
Section: Classical Markers As a Predictor For Clinicopathologic Charamentioning
confidence: 98%
“…Of the 46 articles that were eligible for inclusion, 13 assessed classical NK cell markers. [26][27][28][29][30][31][32][33][34][35][36][37][38] The activating markers group existed of three articles, [39][40][41] the inhibiting markers group of 5 [42][43][44][45][46] and the death receptor group of 25. Figure 1 provides an overview of study selection.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ladányi et al. ( 32 ) observed no correlation between the expression of p16 and the response to iCHT evaluated by CT or MRI. They analyzed the pretreatment biopsy samples from 47 patients with locally advanced oropharynx, hypopharynx, larynx, or oral cavity cancer.…”
Section: Resultsmentioning
confidence: 95%